Take care how you help others listen : sermon listening in an age of distraction - Kim, Sebastian Y. (St. Louis, Missouri : Covenant Theological Seminary, 2017)
1 online resource (PDF (xi, 252 leaves)) : charts; Abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2017; Bibliography: leaves 245-252